The Influence of Dividend Policy, Capital Structure, and ESG Disclosure on Firm Value (An Empirical Study on Non-Financial Companies Listed on the Indonesia Stock Exchange, 2019–2024) - Caronge, Erniyati; Asniwati, Asniwati (Universitas Yapis Papua, 2025)
This study aims to examine the effect of dividend policy, capital structure, and ESG disclosure on firm value in non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The data were obtained from companies’ annual reports and sustainability reports, with a total sample of 50 companies selected using purposive sampling. The analytical method employed was panel data regression with a fixed-effect model. The results show that dividend policy and capital structure have a significant effect on firm value, while ESG disclosure has a positive but insignificant effect. This study provides implications for management in optimizing financial policies to enhance firm value